Visual cues can be sufficient for triggering automatic, reflexlike spatial updating - Riecke, Bernhard E.; Heyde, Markus Von Der; Bülthoff, Heinrich H (ACM Transactions on Applied Perception (TAP), 2005)
“Spatial updating” refers to the process that automatically updates our egocentric mental representation of our immediate surround during self-motions, which is essential for quick and robust spatial orientation. To investigate the relative contribution of visual and vestibular cues to spatial updating, two experiments were performed in a high-end Virtual Reality system. Participants were seated on a motion platform and saw either the surrounding room or a photorealistic virtual model presented via head-mounted display or projection screen. After upright rotations, participants had to point “as accurately and quickly as possibl ” to previously learned targets that were outside of the current field of view (FOV). Spatial updating performance, quantified as response time, configuration error, and pointing error, was comparable in the real and virtual reality conditions when the FOV was matched. Two further results challenge the prevailing basic assumptions about spatial updating: First, automatic, reflexlike spatial updating occurred without any physical motion, i.e., visual information from a known scene alone can, indeed, be sufficient, especially for large FOVs. Second, continuous-motion information is not, in fact, mandatory for spatial updating---merely presenting static images of new orientations proved sufficient, which motivated our distinction between continuous and instant-based spatial updating.
Keywords: Riecke; Riecke_2005; artificial, augmented, and virtual realities; bernhard-riecke; ego-motion simulation; experimentation; iSpaceWeb; journalPaper; markus-von-der-heyde; spatial updating